Descriptive Epidemiology of Adolescent Clavicle Fractures: Results From the FACTS (Function after Adolescent Clavicle Trauma and Surgery) Prospective, Multicenter Cohort Study. Issue 5 (27th May 2020) - Ellis, Henry B.; Li, Ying; Bae, Donald S.; Kalish, Leslie A.; Wilson, Philip L.; Pennock, Andrew T.; Nepple, Jeffrey J.; Willimon, Samuel C.; Spence, David D.; Pandya, Nirav K.; ,; Kocher, Mininder S.; et al.
Background: The majority of previous investigations on operative fixation of clavicle fractures have been related to the adult population, with occasional assessments of the younger, more commonly affected adolescent population. Despite limited prospective data for adolescents, the incidence of operative fixation of adolescent diaphyseal clavicle fractures has increased. Purpose: To detail the demographic features and descriptive epidemiology of a large pooled cohort of adolescent patients with diaphyseal clavicle fractures presenting to pediatric tertiary care centers in the United States through an observational, prospective, multicenter cohort study (Function after Adolescent Clavicle Trauma and Surgery [FACTS]). Study Design: Cross-sectional study; Level of evidence, 4. Methods: Patients aged 10 to 18 years who were treated for a diaphyseal clavicle fracture between August 2013 and February 2016 at 1 of 8 geographically diverse, high-volume, tertiary care pediatric centers were screened. Treatment was rendered by any of the pediatric orthopaedic providers at each of the 8 institutions, which totaled more than 50 different providers. Age, sex, race, ethnicity, fracture laterality, hand dominance, mechanism of injury, injury activity, athletic participation, fracture characteristics, and treatment decisions were prospectively recorded in those who were eligible and consented to enroll. Results: A total of 545 patients were included in the cohort. The mean age of the study population was 14.1 ± 2.1 years, and 79% were male. Fractures occurred on the nondominant side (56%) more frequently than the dominant side (44%). Sport was the predominant activity during which the injury occurred (66%), followed by horseplay (12%) and biking (6%). The primary mechanism of injury was a direct blow/hit to the shoulder (60%). Overall, 54% were completely displaced fractures, defined as fractures with no anatomic cortical contact between fragments. Mean shortening within the completely displaced group was 21.9 mm when measuring the distance between fragment ends (end to end) and 12.4 mm when measuring the distance between the fragment end to the corresponding cortical defect (cortex to corresponding cortex) on the other fragment (ie, true shortening). Comminution was present in 18% of all fractures. While 83% of all clavicle fractures were treated nonoperatively, 32% of completely displaced fractures underwent open reduction and internal fixation. Conclusion: Adolescent clavicle fractures occurred more commonly in male patients during sports, secondary to a direct blow to the shoulder, and on the nondominant side. Slightly more than half of these fractures were completely displaced, and approximately one-fifth were comminuted. Within this large cohort, approximately one-third of patients with completely displaced fractures underwent surgery, allowing for future prospective comparative analyses of radiographic, clinical, and functional outcomes.